Penanaman Rasa Tanggung Jawab dan Sikap Disiplin melalui Pembiasaan Upacara Bendera Siswa Kelas IV Di SD N 2 Ngabean Kabupaten Kendal - Zahro, Devi Fathimatuz; Bektiningsih, Kurniana (Paedagogie, 2026)
The foundation of this study is the paucity of research on the use of flag ceremonies to teach elementary school pupils discipline and responsibility. In actuality, this exercise plays a big part in helping pupils grow as people. The goal of this study is to explain how the practice of flag ceremonies might help fourth-grade kids develop a sense of accountability and discipline, pinpoint challenges in putting these customs into practice, and assess how this activity affects the development of students' character. Participants in this study, which employs a descriptive qualitative methodology, include the principal, class teachers, and fourth-grade pupils at SD N 2 Ngabean who were specifically chosen. Following data collection by observation, interviews, and documentation, source and technical triangulation approaches were used to assess the data's validity. Through active involvement in ceremonial tasks, adherence to rules, and the habit of being disciplined and punctual, the flag ceremonies habit effectively instills a feeling of responsibility and discipline in pupils, according to the study's findings.Disparities in student motivation and a lack of comprehension of the significance of the flag ceremony were among the challenges noted.These results are consistent with the goals of the study and provide credence to the character education hypothesis, which highlights the value of routines and role models in promoting responsibility and discipline. According to the study's findings, regular flag ceremonies can help primary school pupils develop moral principles if they are accompanied by their teachers. The study's implications include enhancing character education research and offering useful advice to educators and schools on how to best use flag ceremonies as a character-building tool.